Popular rice (Oryza sativa L.) cultivars show contrasting responses to heat stress at gametogenesis and anthesis - Shi, W.; Ishimaru, T.; Gannaban, R.B.; Oane, W.; Jagadish, S.V.K. (Wiley, 2015)
Studies on heat tolerance in rice (Oryza sativa L.) have focused on a range of accessions that are currently not grown or cultivated in small localized geographic regions, while popular rice cultivars occupying millions of hectares have not been tested for their response to heat stress. Hence, 18 popular rice cultivars grown across tropical and subtropical regions were subjected to 38°C for 6 h of heat stress at anthesis and five selected contrasting entries were exposed to six consecutive days (6 h each day) of stress coinciding with both gametogenesis and anthesis. Among the tested entries, Ciherang was the most tolerant, after both 6 h at anthesis and 6 d of stress across both gametogenesis and anthesis, whereas Moroberekan and KDML‐105 were the most susceptible. Using a quick and easy phenotyping protocol and by considering all the sterile spikelets across target panicles, the crucial physiological window “spikelets with exserted anthers but with no ovule enlargement” was identified as the most sensitive stage with exposure to heat stress at both critical reproductive stages. Geographic origin of rice varieties was not clearly related to the degree of tolerance or susceptibility to heat stress because both conditions were observed in cultivars from each target region. Our findings complement other ongoing efforts that are using heat‐tolerant landraces and wild rice as donors to further increase tolerance to sustain global rice production under future warmer climate.